E-Book dengan Memanfaatkan Flipbook Maker sebagai Multimedia pada Pembelajaran Berbasis E-Newspaper Literacy dalam Mengoptimalkan Critical Thinking Skills di Perguruan Tinggi - Dessi Susanti; Armiati Armiati; Rose Rahmidani; Sulikah Sulikah; Vivi Rizky Aulya; Finky’an Syafana Putri; Jelli Anggraini (Universitas Negeri Padang, 2022)
It is necessary to provide ebooks as textbooks for the Introduction to Accounting course which is a learning medium to accommodate the diverse characteristics of students and is equipped with cases according to students' real lives in order to optimize their Critical Thinking. So that research was carried out in 2021, which produced an ebook with Flipbook Maker Based on E_Newspaper Literacy in Optimizing Critical Thinking for students in Higher Education which is valid and practical in the Introduction to Accounting course. To continue the 2021 research phase, it is necessary to carry out research in 2022 as a follow-up stage, namely the Assessment Phase, which is the stage of implementation and evaluation of the Ebook with Flipbook Maker that has been produced. Research activities in 2022 are assessing the success of using ebooks with E_Newspaper Literacy-based Flipbook Maker in improving students' critical thinking through action research. This classroom action research aims to implement an Ebook using a Flipbook Maker Based on E_Newspaper Literacy through the Case Method in an Introduction to Accounting class with 25 students. The successful use of Ebooks can be seen from the achievement of students' critical thinking skills which have exceeded the set target of ≥ 60%.